The Implementation Strategy of Non-Cash Payment Systems in The Islamic Boarding School Through Analytical Hierarchy Process Approach - Nafis, Ahmad Ghifary Rizalun; Binti Zainol, Nurfatin Nazilah; Millaturrofi'ah, Millaturrofi'ah (Economica: Jurnal Ekonomi Islam, 2021)
Abstract: This study aimed to observe the problems of non-cash payments implementation in Islamic boarding schools. This research uses descriptive qualitative-quantitative by using the analytical hierarchy process development model (AHP). The results indicated the three most dominant problems, including resources, communication, and governance systems. The literature review and interview results could detail the three main aspects, then examined using AHP. The results showed that these three aspects have priority values with a percentage of the resource aspect is 40%, 38% for the communication aspect, and 22% for the governance system aspect. This study uses primary data through interviews (in-depth interviews) with the experts and practitioners who understand the issues discussed, followed by filling out questionnaires to respondents at the second meeting. This study discusses the analysis of the problem and the main factors in the implementation of non-cash payments in Islamic boarding schools. No previous studies have made Islamic boarding schools the object of research. This research contributes to stakeholders in making policies if they will implement non-cash payments in Islamic boarding schools. Abstrak: Penelitian ini bertujuan untuk mengalisis masalah dan faktor utama yang menghambat jika akan diimplementasikan di pondok pesantren. Penelitian ini menggunakan deskritif kualitatif-kuantitatif dengan menggunakan model pengembangan analytical hierarchy process (AHP). Hasilnya menyimpulkan bahwa terdapat tiga masalah utama pada yang paling dominan yaitu masalah sumber daya, komunikasi dan sistem tata kelola. Kajian literatur dan hasil wawancara dapat merinci tiga aspek utama tersebut yang kemudian diteliti menggunakan AHP. Hasil mengemukakan bahwa ketiga aspek tersebut memiliki nilai prioritas dengan presentase aspek sumber daya sebesar 40%, aspek komunikasi sebesar 38% dan aspek sistem tata kelola sebesar 22%. Data primer melalui wawancara (indepth interview) dengan pakar dan praktisi, yang memiliki pemahaman tentang permasalahan yang dibahas yang dilanjutkan dengan pengisian kuesioner pada responden di pertemuan kedua. Penelitian ini membahas tentang analisis masalah dan faktor utama dalam pelaksanaan pembayaran nontunai di pondok pesantren. Belum ada penelitian sebelumnya yang menjadikan pesantren sebagai objek penelitian. Penelitian ini memberikan kontribusi kepada para stakeholder dalam membuat kebijakan jika menerapkan pembayaran nontunai di pondok pesantren.